Water level in tank using level sensor and PID controller - Abdullah, Muhd Asran (2008)
Water level in tank control using level sensor and PID controller system is an implementation of PID controller application into designing an intelligent and automatic level control of water/liquids/solids. While people especially in engineering fields have difficulties to measure and control the desired level in smooth transitions, this system provides the features which allow people to control and maintain water level in tanks as accurately and as steady with smooth transition process. This system is able to continuously maintain and doing necessary processes non stop day and night. The design will be implemented into a model built for a FKEE process laboratory in UMP (University Malaysia Pahang).